The act in context in contextual therapies - Menegatti, Claudia Lucia (Perspectivas em Análise do Comportamento, 2025)
The act in context is presented in the basic texts of contextual therapies as a metaphor for the entire behavioral event, in continuous flow, and as an innovation for therapeutic applications. The discussion proposed in this essay aims to review possible relationships between Radical Behaviorism and contextual therapies (third generation), rescuing principles proposed by Skinner. Next, the article directs the discussion to three points in which contextual therapies improve and innovate in clinical behavioral practice, namely, the analysis of verbal phenomena in psychotherapy, the contextualized study of the therapeutic relationship and the centrality of functional behavior analysis in the psychotherapeutic process. Finally, it is alerted to the need for knowledge of radical behaviorism as a foundation for the practice of a contextual therapist.